Early evaluation of a powered transfemoral prosthesis with force-modulated impedance control and energy regeneration. (February 2022) - Warner, Holly; Khalaf, Poya; Richter, Hanz; Simon, Dan; Hardin, Elizabeth; van den Bogert, Antonie J.
Highlights: Initial feasibility study for novel powered prosthetic knee. Impedance controller and device both designed for energy regeneration. Simplified control tuning (5 gains) relative to current literature (45 gains). Controller demonstrates capacity for continuous speed adaptation. Self-powered operation achieved under walking gait during pilot study. Abstract: Individuals with an above-knee (AK) amputation typically use passive prostheses, whether reactive (microprocessor) or purely mechanical. Though sufficient for walking, these solutions lack the positive power generation observed in able-bodied individuals. Active (powered) prostheses can provide positive power but suffer complex control and limited energy storage capacities. These shortcomings motivate the development of an active prosthesis implementing a novel impedance controller design with energy regeneration. The controller requires only five tuning parameters that are intuitive to adjust in contrast to the current standard—finite state machine impedance scheduling of up to 45 gains. This simplification is uniquely achieved by modulating knee joint impedance by axial shank force. Furthermore, the proposed control approach introduces analytical guidance for impedance tuning to purposely integrate energy regeneration; specifically, a precise amount of negative damping is injected into the joint. A pilot study conducted with a volunteer with an AK amputation walking at three distinct speeds and at continually self-selected varying speeds demonstrated the adaptability of the controller to changes in speed. Self-powered operation was attained for all trials despite low mechanical component efficiencies. These early results suggest the efficacy of simplifying impedance control tuning and fusing control and energy regeneration in transfemoral prostheses.